2015
DOI: 10.3171/2015.2.focus14849
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surgical correction on white matter microstructural integrity in rabbits with familial coronal suture craniosynostosis

Abstract: OBJECT Craniosynostosis is a condition in which one or more of the calvarial sutures fuses prematurely. In addition to the cosmetic ramifications attributable to premature suture fusion, aberrations in neurophysiological parameters are seen, which may result in more significant damage. This work examines the microstructural integrity of white matter, using diffusion tensor imaging (DTI) in a homogeneous strain of rabbits with simple, familial coronal suture synostosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…While direct neurohistopathological analysis was beyond the scope of the present study, previous results from this rabbit model have shown that early suturectomy resulted in the preservation of white matter integrity as assessed by diffusion tensor imaging (DTI) [ 17 ], an increase in intracranial volume and a normalization of brain surface morphology as assessed with CT-imaging, and a normalization of cranial vault and cranial base angulation as assessed radiographically [ 13 , 23 , 24 , 45 , 46 , 47 ]. Furthermore, studies have shown reossification of the suture following suturectomy can halt the initial improvements in intracranial volume and brain morphology after suturectomy, and further research has aimed to prevent reossification of the suture through molecular therapies [ 47 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While direct neurohistopathological analysis was beyond the scope of the present study, previous results from this rabbit model have shown that early suturectomy resulted in the preservation of white matter integrity as assessed by diffusion tensor imaging (DTI) [ 17 ], an increase in intracranial volume and a normalization of brain surface morphology as assessed with CT-imaging, and a normalization of cranial vault and cranial base angulation as assessed radiographically [ 13 , 23 , 24 , 45 , 46 , 47 ]. Furthermore, studies have shown reossification of the suture following suturectomy can halt the initial improvements in intracranial volume and brain morphology after suturectomy, and further research has aimed to prevent reossification of the suture through molecular therapies [ 47 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our well-established rabbit model of familial coronal suture synostosis [ 9 – 13 , 17 , 21 , 25 , 51 ] was used due to the similarity in the sutural, cranial vault, and cerebrovascular architecture dysmorphology, compared to infants with craniosynostosis [ 13 , 21 , 23 , 39 , 48 – 50 , 52 54 ]; however, we acknowledge the limitation of extrapolating these results to a human clinical setting given the differences in brain morphology and growth patterns between humans and lagomorphs. Approximately 90% of brain growth in rabbits is completed by 35 days of age [ 13 , 55 ], as compared to about 4 to 6 years of age in humans [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations